MRI visible Fe3O4 polypropylene mesh: 3D reconstruction of spatial relation to bony pelvis and neurovascular structures - Chen, Luyun; Sohn, Christof; Brocker, Kerstin A. (International urogynecology journal, 2017)
Introduction and hypothesisTo demonstrate mesh magnetic resonance imaging (MRI) visibility in living women, the feasibility of reconstructing the full mesh course in 3D, and to document its spatial relationship to pelvic anatomical structures.MethodsThis is a proof of concept study of three patients from a prospective multi-center trial evaluating women with anterior vaginal mesh repair using a MRI-visible Fe3O4 polypropylene implant for pelvic floor reconstruction. High-resolution sagittal T2-weighted (T2w) sequences, transverse T1-weighted (T1w) FLASH 2D, and transverse T1w FLASH 3D sequences were performed to evaluate Fe3O4 polypropylene mesh MRI visibility and overall post-surgical pelvic anatomy 3 months after reconstructive surgery. Full mesh course in addition to important pelvic structures were reconstructed using the 3D Slicer® software program based on T1w and T2w MRI.ResultsThree women with POP-Q grade III cystoceles were successfully treated with a partially absorbable MRI-visible anterior vaginal mesh with six fixation arms and showed no recurrent cystocele at the 3-month follow-up examination. The course of mesh in the pelvis was visible on MRI in all three women. The mesh body and arms could be reconstructed allowing visualization of the full course of the mesh in relationship to important pelvic structures such as the obturator or pudendal vessel nerve bundles in 3D.ConclusionsThe use of MRI-visible Fe3O4 polypropylene meshes in combination with post-surgical 3D reconstruction of the mesh and adjacent structures is feasible suggesting that it might be a useful tool for evaluating mesh complications more precisely and a valuable interactive feedback tool for surgeons and mesh design engineers.